Screening of wheat (Triticum aestivum) variesties tolerant to manganese- deficency stress - BANSAL, R L; NAYYAR, V K (The Indian Journal of Agricultural Sciences, 2013)
Manganese deficiency is a problem in bread wheat (Triticum aestivum L. emend. Fiori & Paol.) production whengrown on highly permeable sandy soils cropped with rice (Oryza sativa L.) for 5 or more years. The variation in theability of wheat varieties to maintain yield on soils with limited Mn availability was investigated. A field experimentwas conducted during winter season (rabi) 1995-96 to study tbe tolerance of6 varieties of wheat to manganese stressin a Mn-deficient field containing 2.2 mg DTPA-Mn/kg soil. The treanments included control and 3 foliar sprays of0.5% manganese sulphate solution. All the varieties responded to foliar application of Mn and tbe increase in grainyield varied from 0.30 to 0.85 tonnes/ha. The macaroni (Triticum durum Desf.) varieties of wheat responded more toMn (26.4-34.9%) than the Triticum aestivum varieties (7.9-23.0%). Based on tbe increase (%) in grain yield on foliarapplication of Mn, the varieties were grouped least tolerant (,PBW 34' and 'PDW 215'), moderately tolerant (,PBW226' and 'PBW 343') and tolerant (,WH 542' and 'HD 2329'). The grain yield was significantly related with both Mnconcentration in flag-leaf (r = 0.80*) and Mn uptake (r = 0.92**).